Diversity patterns of selected Andean plant groups correspond to topography and habitat dynamics, not orogeny - Mutke, Jens; Jacobs, Rana; Meyers, Katharina; Henning, Tilo; Weigend, Maximilian (Frontiers in Genetics, 2014)
The tropical Andes are a hotspot of biodiversity, but detailed altitudinal and latitudinal distribution patterns of species are poorly understood. We compare the distribution and diversity patterns of four Andean plant groups on the basis of georeferenced specimen data: the genus Nasa (Loasaceae), the two South American sections of Ribes (sect. Parilla and sect. Andina, Grossulariaceae), and the American clade of Urtica (Urticaceae). In the tropical Andes, these often grow together, especially in (naturally or anthropogenically) disturbed or secondary vegetation at middle to upper elevations. The climatic niches of the tropical groups studied here are relatively similar in temperature and temperature seasonality, but do differ in moisture seasonality. The Amotape-Huancabamba Zone (AHZ) between 3–8° S shows a clear diversity peak of overall species richness as well as for narrowly endemic species across the groups studied. For Nasa, we also show a particular diversity of growth forms in the AHZ. This can be interpreted as proxy for a high diversity of ecological niches based on high spatial habitat heterogeneity in this zone. Latitudinal ranges are generally larger towards the margins of overall range of the group. Species number and number of endemic species of our taxa peak at elevations of 2,500–3,500 m in the tropical Andes. Altitudinal diversity patterns correspond well with the altitudinal distribution of slope inclination. We hypothesize that the likelihood and frequency of landslides at steeper slopes translates into temporal habitat heterogeneity. The frequency of landslides may be causally connected to diversification especially for the numerous early colonizing taxa, such as Urtica and annual species of Nasa. In contrast to earlier hypotheses, uplift history is not reflected in the pattern here retrieved, since the AHZ is the area of the most recent Andean uplift. Similarly, a barrier effect of the low-lying Huancabamba depression is not retrieved in our d